Pengaruh Tingkat Suku Bunga Kredit, Promosi, Dan Kualitas Pelayanan Terhadap Kepuasan Anggota Koperasi Lamalepa Maju Jaya Abadi Di Kota Batam - Bali , Adrianus Loli; Nuraeni , Brigida Endah; Harianja , Josepin (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This study aims to determine the effect of credit interest rates, promotions and service quality on member satisfaction at Lamalepa Maju Jaya Abadi cooperative in Batam City both partially and simultaneously. This study uses a quantitative method by distributing questionnaires to 66 members of the Lamalepa MJA cooperative. Data processing in this study uses SPSS version 26. The results of data processing on the credit interest rate variable found that t count was 1.698 > t table of 1.669 with a significance level of 017 < 0.05, so the credit interest rate did have a positive and significant effect on member satisfaction. The promotion variable had a t count of 2.644 > t table of 1.669 with a significance level of 010 < 0.05, so the promotion did have a positive and significant effect on member satisfaction. The service quality variable has a calculated t of 4,424 > ttable 1.669 with a significance level of 000 < 0.05, indicating that service quality does have a positive and significant effect on member satisfaction. The f-test shows that the calculated f-value for loan interest rates, promotions, and service quality is 14.000 > fttable 2.79 with a significance level of 000 < 0.05. The R2 test shows that loan interest rates, promotions, and service quality contribute 40.0% to member satisfaction, while the remaining 60.0% is influenced by other independent variables not explained in this study